The bio-psychosocial implications of unemployment for rural young women in South Africa: revelations from Cassel, Northern Cape Province - Misheck, Dube (Penerbit Universiti Kebangsaan Malaysia, 2020)
The reality of unemployment in South Africa has become a buzz word for the social work profession in tandem with agendas for political parties in their manifestos in the country. For the doubters of political interpretations, the problem seems to have superficial political agendas yet professional analysts have also lamented to its dire bio-psychosocial consequences for the rural young women in South Africa. This paper exposes the bio-psychosocial implications of unemployment for the young women in Cassel in the Northern Cape Province in South Africa. The study employed a qualitative approach which purposely selected eleven unemployed young women between the ages of fifteen and thirty five to provide data saturation point and reveal the bio-psychosocial consequences of unemployment. Thematic data analysis was used which provided significant emergent themes for the study. The findings were that unemployed rural young women are prone to a host of bio-psychosocial problems including alcohol and drug addiction, commercial sex work and associated diseases, family disputes and resentment, homelessness and suicidal thoughts. Deliberate social work interventions have been found to be monumentally lacking yet overtly needed. The paper recommends various social work intervention strategies to help ameliorate the eminent bio-psychosocial problems facing young women in the rural areas of the North West Province.